PERANAN ZAKAT PRODUKTIF DALAM PEMBERDAYAAN MASYARAKAT MISKIN (Studi kasus pada Badan Amil Zakat (BAZ) Kabupaten Kebumen) - Pambudi, Hidayat Aji (P4M STIE Putra Bangsa, 2013)
With the obligation of zakat, allow the poor to participate in public life as well as carrying out its obligations in worship to God, and help to establish the social order. In addition, they also feel as a part of society and not be marginalized by communities in society . Zakat by some Islamic leaders, is considered as a solution for achieving justice for society, particularly economic justice. With the charity, the prosperity of society are expected to further increase or reduce the level of poverty. Besides widening economic inequality has not increased resulting in social tension. This condition could be realized if the charity actually issued by the Moslems who can afford it. Data in 2011 and in 2012 Kebumen district is one of the districts with the highest poverty rates in Central Java. From this fact to note how much influence the productive charity revolving fund to contribute to the alleviation of the poverty high. In addition to determine the effect of charity productive revolving fund research also analyzes the impact on the level of income, consumption, savings and donation before and after receiving productive zakat. The results of this study is known earning charity, supervision and mentoring effect on income, consumption, savings and mustahik infak. Keywords : zakat productive , income , community empowerment , the poor